Microscopic damage evolution and physical–mechanical behavior of high-temperature red sandstone under varying heating and cooling durations - Mingze Qin; Yue Su; Xiaolan Wang; Huawu Niu; Yifan Zhang; Dongxu Zhang; Nan Qin (Scientific Reports)
Abstract The investigation into the cooling and heating duration is crucial for evaluating the aftermath of a fire incident. This study comprehensively analyzes the macroscopic and microscopic characteristics of red sandstone under high temperatures, heating, and cooling conditions, with temperatures ranging from 200 to 800 °C and heating/cooling durations ranging from 0.75 to 3 h and 0.5 to 54 h, respectively XRD and SEM techniques were employed to investigate mineral composition and microstructural changes. Multifactorial experiments explored the impact of these conditions on the rock’s physical properties and assessed mechanical properties such as peak stress, peak strain, and elastic modulus. Data fitting with MATLAB was used to construct a damage constitutive model. The findings show that elevated temperatures and prolonged heating significantly alter the microstructure and composition of red sandstone, including pore formation, void development, and structural modifications. Heating induces cracking, voids, and chemical reactions, with extended exposure leading to changes in feldspar minerals (K/Ca/Na). Temperature-dependent physical properties exhibit mass loss and density decline. Mechanical properties are substantially affected, with peak stress decreasing from 40 MPa to 6.94 MPa, and variations in peak strain and elastic modulus. Thermal stress at specific temperatures notably enhances compressive strength. The newly established constitutive model has an error within 5% compared to actual experimental results.